2007
DOI: 10.4049/jimmunol.178.11.7267
|View full text |Cite
|
Sign up to set email alerts
|

Early Virus-Associated Bystander Events Affect the Fitness of the CD8 T Cell Response to Persistent Virus Infection

Abstract: Chronic Ag exposure during persistent viral infection erodes virus-specific CD8 T cell numbers and effector function, with a concomitant loss of pathogen control. Less clear are the respective contributions of Ag-specific and Ag-nonspecific (bystander) events on the quantity, quality, and maintenance of antiviral CD8 T cells responding to persistent virus infection. In this study, we show that low-dose inoculation with mouse polyomavirus (PyV) elicits a delayed, but numerically equivalent, antiviral CD8 T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 61 publications
1
27
1
Order By: Relevance
“…The small and large fragments were excised from pUC19, ligated to generate full-length PyV DNA, and transfected (using Lipofectamine 2000 [Invitrogen]) into baby mouse kidney cells. Recombinant vesicular stomatitis virus encoding the D b -restricted LT359-368 epitope (rVSV-LT359) was generated as described previously (2). The tail veins of the mice were injected intravenously (i.v.)…”
Section: Methodsmentioning
confidence: 99%
“…The small and large fragments were excised from pUC19, ligated to generate full-length PyV DNA, and transfected (using Lipofectamine 2000 [Invitrogen]) into baby mouse kidney cells. Recombinant vesicular stomatitis virus encoding the D b -restricted LT359-368 epitope (rVSV-LT359) was generated as described previously (2). The tail veins of the mice were injected intravenously (i.v.)…”
Section: Methodsmentioning
confidence: 99%
“…LP strains of MPyV disseminate more extensively than do SP strains (5,6). Administration of a low dose of the LP strain A2 delays the kinetics of expansion, but not the magnitude, of the MPyV-specific CD8 T cell response (23). We therefore asked whether B6 mice infected with an LP strain (A2) or an SP strain (RA) showed differences in viral dissemination and in the magnitude of the strongly dominant D b -restricted CD8 T cell response to amino acids 359 to 368 of the large T (LT) antigen, designated D b LT359 (48).…”
Section: Resultsmentioning
confidence: 99%
“…A2 and MPyV.LT206 have similar growth kinetics in vitro and in vivo (22). A recombinant vesicular stomatitis virus carrying the LT359 -368 sequence (rVSV-LT359) was generated as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present finding that unhelped memory MT389-specific CD8 ϩ T cells (which do not express CD94/NKG2A) do not expand following Ag challenge provides additional support for the idea that CD94/NKG2A identifies a subpopulation of proliferation-competent antiviral memory CD8 ϩ T cells. We and others have shown that inflammation is detrimental to the differentiation of Ag-specific effector and memory CD8 ϩ T cells (1,3,4). Recently, Badovinac and Harty suggested that the degree of inflammation elicited by microbial infection is directly proportional to the duration and magnitude of the effector phase of the CD8 ϩ T-cell response (3).…”
Section: Discussionmentioning
confidence: 99%